Old Henry [videorecording (Blu-Ray)] - Nelson, Tim Blake; Haze, Scott; Lewis, Gavin; Adkins, Trace (Shout! Factory, 2021)
An action western about a farmer who takes in an injured man with a satchel of cash. Defending a siege, he reveals a gunslinging talent calling his true identity into question.